Ultrassonografia para bloqueios periféricos em crianças: revisão sistemática e metanálise de ensaios clínicos randonizados - Cabral, Lucas Wynne [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Background: it has been suggested that ultrasound-guided regional anesthesia could improve the blockade efficacy and decrease complication rates in the pediatric population, but this hypothesis has not previously been adequately tested in a quantitative manner. Aim: the purpose of this systematic review of randomized clinical trials (RCT) is to assess whether the use of ultrasonography in the pediatric population has advantages over any other method of nerve location, such as the anatomical landmark-based technique, paraesthesia or use of an electrical nerve stimulator. Methods: the systematic search, data extraction, critical appraisal and pooled analysis were performed according to the Cochrane Handbook and PRISMA guidelines. The search strategy included the CENTRAL of the Cochrane Library, Medline, EMBASE, and Lilacs. The date of the last search was November 5, 2014. The relative risk (RR), mean difference (MD) and their corresponding 95% confidence intervals (95% CIs) were calculated using the Revman statistical software for dichotomous and continuous outcomes, respectively. Results: eleven randomized, clinical, controlled trials (published between 2004 and 2013) with a total 634 patients met the inclusion criteria. The methodological quality of the included studies was considered regular. There was a slight benefit of ultrasound to the success rate (RR 1.19, 95% CI 1.07 to 1.33), which was variable according to the anatomical region studied and a more important reduction of the analgesia requirement in the postoperative period with the use of ultrasound for peripheral nerve blocks (RR 0.2, 95% CI 0.11-0.34). There was only one complication reported (blood vessel puncture in one control group). Conclusions: there is moderate evidence that the use of ultrasound-guided peripheral nerve block in children reduces the number of patients requiring additional analgesia in the postoperative period and ...

Introdução: acredita-se que a anestesia regional guiada por ultrassonografia (USG) pode melhorar a eficácia dos bloqueios de nervos periféricos e reduzir as complicações na população pediátrica, porém essa hipótese ainda não foi previamente testada de forma quantitativa. Objetivo: a proposta desta revisão sistemática de ensaios clínicos randomizados (ECR) foi avaliar se o uso da ultrassonografia em pediatria melhoraria a taxa de sucesso dos bloqueios e reduziria o índice de complicações comparativamente a outros métodos tradicionais de localização de nervos. Métodos: a pesquisa sistemática, extração dos dados, avaliação crítica e análise conjunta dos dados seguiram as recomendações para a realização de revisões sistemáticas propostas pela Colaboração Cochrane e pela declaração PRISMA. A estratégia de busca incluiu as bases CENTRAL, EMBASE, Medline e Lilacs. A última pesquisa foi realizada em novembro de 2014. O risco relativo (RR) e a diferença média (DM), com seus respectivos intervalos de confiança de 95% (IC 95%), foram calculados utilizando-se o programa estatístico Revman para dados dicotômicos e contínuos, respectivamente. Resultados: onze ensaios clínicos randomizados, publicados entre 2004 e 2013, perfazendo um total de 634 pacientes, cumpriram os critérios de inclusão. A qualidade metodológica foi considerada moderada. Houve um pequeno benefício da ultrassonografia na taxa de sucesso (RR 1,19; IC 95% 1,07-1,32) que foi variável de acordo com a região anatômica avaliada, associado a uma redução na necessidade de analgesia no pós-operatório com o uso da ultrassonografia (RR 0,2; IC 95% 0,11-0,34). Apenas uma complicação foi reportada nos estudos incluídos. Uma punção vascular em um paciente do grupo controle durante realização do bloqueio ílio-inguinal/ílio-hipogástrico (II/IH). Conclusão: existe moderada evidência de que a ultrassonografia quando utilizada para...
Ultrasound guided nerve blockade in children : a meta-analysis of randonized clinical trials
Keywords: Criança; Ultrassonografia; Bloqueio nervoso; Anestesia por condução; Ensaios clínicos; Pediatria; Revisão; Conduction anesthesia; Ultrasonic imaging